Reducing the information gap on loricarioidei (Siluriformes) mitochondrial genomics - Moreira, Daniel Andrade (2020)
Background: The genetic diversity of Neotropical fish fauna is underrepresented in public databases. This distortion is evident for the order Siluriformes, in which the suborders Siluroidei and Loricarioidei share equivalent proportion of species, although far less is known about the genetics of the latter clade, endemic to the Neotropical Region. Recently, this information gap was evident in a study about the structural diversity of fish mitochondrial genomes, and hampered a precise chronological resolution of Siluriformes. It has also prevented molecular ecology investigations about these catfishes, their interactions with the environment, responses to anthropogenic changes and potential uses. Results: Using high-throughput sequencing, we provide the nearly complete mitochondrial genomes for 26 Loricariidae and one Callichthyidae species. Structural features were highly conserved. A notable exception was identified in the monophyletic clade comprising species of the Hemiancistrus, Hypostomini and Peckoltia-clades, a ~60 nucleotide-long deletion encompassing the seven nucleotides at the 3' end of the Conserved Sequence Block (CSB) D of the control region. The expression of mitochondrial genes followed the usual punctuation pattern. Heteroplasmic sites were identified in most species. The retrieved phylogeny strongly corroborates the currently accepted tree, although bringing to debate the relationship between Schizolecis guntheri and Pareiorhaphis garbei, and highlighting the low genetic variability within the Peckoltia-clade, an eco-morphologically diverse and taxonomically problematic group. Conclusions: Herein we have launched the use of high-throughput mitochondrial genomics in the studies of the Loricarioidei species. The new genomic resources reduce the information gap on the molecular diversity of Neotropical fish fauna, impacting the capacity to investigate a variety of aspects of the molecular ecology and evolution of these fishes. Additionally, the species showing the partial CSB-D are candidate models to study the replication and transcription of vertebrate mitochondrial genome. © 2017 The Author(s).